Technology Acceptance Model pada Sistem Informasi Akademik berbasis Web - Yovita Kinanti Kumarahadi; Kumaratih Sandradewi (Jurnal Ilmiah SINUS, 2021)
Academic information system is an important system in students learning’s activities because it’s used as connector between students and lecturers. In addition, academic information system also acts as a liaison between lecturers and other relevant external parties. Academic information system provides several services, both for students and lecturers. These facilities include the provision of information on study plans, grades, schedules, and courses. However, only a few facilities are frequently used so that the use of the academic information system is not optimal.The problem in this study is the need for an evaluation to determine the acceptance of the academic information system by users, so that the system can be improved and developed. This study aims to determine the acceptance of web-based academic information system by users at STMIK Sinar Nusantara Surakarta with the Technology Acceptance Model or TAM.